Teacher Roles in Promoting Out-Of-Class Learning: Lessons from a Spanish For Specific Purposes Course - Diego Mideros (Studies in Self-Access Learning Journal)
In this paper, I discuss a small-scale case study that explores the important role teachers play in promoting out-of-class learning among their students. Data come from in-depth interviews with three of the teachers who delivered a Spanish for specific purposes blended course. I explored the different ways in which these teachers went about encouraging students to engage with the online segment of the course. The study is mainly informed by the notion of affordances (Cotterall, 2017; Murray, 2017; van Lier, 2004) and the growing body of literature on learning beyond the classroom (LBC) (Benson, 2011; Reinders & Benson, 2017; Reinders, 2020) where teachers play a pivotal role in promoting out-of-class learning. The main takeaway from this study is that for teachers to promote out-of-class learning, they should first identify the learning possibilities available in whatever materials students are to use outside of the classroom. In the case of this study, teachers had to promote the use of the learning platform that students were supposed to engage with as part of their out-of-class learning segment of the course. However, I found that only one teacher fully promoted out-of-class learning simply because she saw value in the platform and was able to help students see such value as well. The opposite was also true; the other two teachers did not seem to see much value in the platform and as a result, they were not entirely successful in promoting out-of-class learning among their students.